2020
DOI: 10.1016/j.chest.2020.08.564
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid Treatment in Patients With Severe Covid-19 Pneumonia

Abstract: SARS-CoV2 is known for causing atypical pneumonia with rapidly progressive respiratory failure requiring intubation. Usage of steroids have been shown to be of benefit in similar disease processes caused by other coronaviruses specifically SARS/MERS. Currently in the literature there is lack of consensus regarding steroids use in severely ill patients with COVID-19 pneumonia. We conducted a retrospective analysis to evaluate the efficacy of systemic corticosteroids and outcomes in COVID-19 patients with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Data were highly heterogenous (I 2 = 91%; P < 0.00001). Corticosteroids reduced the risk of intubation in one study [ 14 ], while increasing the risk in another [ 32 ], and they had no impact on intubation in the third study [ 33 ]. Unfortunately, only one study addressed the necessity of endotracheal intubation as an outcome variable that showed a significant reduction of intubation in patients treated with corticosteroids (P = 0.02) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…Data were highly heterogenous (I 2 = 91%; P < 0.00001). Corticosteroids reduced the risk of intubation in one study [ 14 ], while increasing the risk in another [ 32 ], and they had no impact on intubation in the third study [ 33 ]. Unfortunately, only one study addressed the necessity of endotracheal intubation as an outcome variable that showed a significant reduction of intubation in patients treated with corticosteroids (P = 0.02) [ 14 ].…”
Section: Resultsmentioning
confidence: 99%
“…In some DMD cases, the dose of corticosteroids should be increased in order to meet standard infection/stress steroid protocols [16] when febrile illness begins. Recent studies support the benefit of corticosteroid usage in the treatment of COVID-19 patients [22], as an early course of corticosteroids may attenuate progression to the hyperinflammation phase of COVID-19 that requires an escalation of care [23]. It is not known whether chronic corticosteroid treatment may protect from severe COVID-19 disease.…”
Section: Discussionmentioning
confidence: 99%
“…All 24 of our selected articles compared outcomes of corticosteroid with the control group and our primary outcome mortality was recorded in all 24 studies [13,30,[39][40][41][42][43][44][45][46][47][48]31,[49][50][51][52][32][33][34][35][36][37][38].…”
Section: Description Of the Selected Studiesmentioning
confidence: 99%
“…Length of hospital stay (days) was analyzed in 3 studies [13,48,50], secondary infection rate was recorded in 12 studies [32,37,50,51,[42][43][44][45][46][47][48][49], length of mechanical ventilation was recorded in 5 studies [39,42,[49][50][51], number of patients in mechanical ventilation (MV) was presented in 14 studies [13,31,48,50,51,33,34,38,41,42,[45][46][47], length of ICU stay (days) was reported in 6 studies [13,43,[48][49][50][51]. Twenty-three articles included patients with the respiratory viral infection and one article included patients with acute respiratory distress syndrome.…”
Section: Description Of the Selected Studiesmentioning
confidence: 99%